Deletion of discoidin domain receptor 2 attenuates renal interstitial fibrosis in a murine unilateral ureteral obstruction model. (1st January 2019) - Li, Xi'an; Bu, Xin; Yan, Fei; Wang, Fuli; Wei, Di; Yuan, Jiarui; Zheng, Wanxiang; Su, Jin; Yuan, Jianlin
Abstract: Background: Renal interstitial fibrosis is a common pathway of chronic kidney disease to end-stage renal disease, which is characterized by an imbalance between the synthesis and degradation of the collagen-rich extracellular matrix (ECM). While, discoidin domain receptor 2 (DDR2) can be activated when it binds to some types of collagen. Therefore, we hypothesized that DDR2 may be a major player in renal interstitial fibrosis. Methods: Renal histologic analysis, real-time PCR analyses and hydroxyproline assay were performed in DDR2-deficient mice and wild-type mice after unilateral ureteral obstruction; C57 mice were randomly divided into sham operation group (Sham group, n  = 4), renal interstitial fibrosis model group (UUO group, n  = 4), and calcium dobesilate treatment group (CDT group, n  = 4), preparation of renal interstitial fibrosis model by unilateral ureteral obstruction (UUO), CDT Group was treated with calcium dobesilate orally, Sham group and UUO group were given double distilled water, HE staining, Masson staining, real-time quantitative PCR were detected after 14 days of UUO in mice to observe the renal interstitial fibrosis degree. Results: DDR2 expression was dramatically increased in the obstructed kidney; In contrast to wild-type mice that developed severe interstitial fibrosis, the DDR2-deficient mice displayed only moderate fibrotic changes; Compared with the UUO group, the degree of renal interstitial fibrosis in CDT group was relieved after operation 14 day. Conclusion: DDR2 might play an important role in the development of RIF; Calcium dobesilate can affect the expression of DDR2 and improve the renal interstitial fibrosis in mice.